Viscoplastic Modeling of a Novel Lightweight Biopolymer Drilling Fluid for Underbalanced Drilling - Khalil, M.; Mohamed Jan, B. (American Chemical Society, 2012)
This paper presents a concise investigation of viscoplastic behavior of a novel lightweight biopolymer drilling fluid. Eight different rheological models namely the Bingham plastic model, Ostwald–De–Weale model, Herschel–Bulkley model, Casson model, Sisko model, Robertson–Stiff model, Heinz–Casson model, and Mizhari–Berk model were used to fit the experimental data. The effect of concentration of clay, glass bubbles, starch, and xanthan gum on the fluid rheological properties was investigated. Results show that the fitting process is able to successfully predict the rheological behavior of the fluid very well. The predicted values calculated from the best selected model are in a good agreement with the experimental data both in low and high (1500 s–1) rate of shear. The result also indicated that the presence of clay, glass bubbles, and xanthan gum have significantly changed the fluid behavior, while the presence of starch has not. Results also showed that all of the tested fluid seems to follow pseudoplastic behavior except for the following three tested fluids: one is fluid with the absence of clay, second and third is fluids with no glass bubble or xanthan gum, respectively. The first fluid tends to follows a Newtonian behavior, while the other two fluids tend to follow dilatants behavior.